A modified technique of transperitoneal direct approach for totally laparoscopic aortoiliac surgery - Stádler, P; Sebesta, P; Vitásek, P; Matous, P; El Samman, K (European journal of vascular and endovascular surgery, 2006)
OBJECTIVE: To present our modification of the transperitoneal direct approach (TDA) for totally laparoscopic aortoiliac surgery. METHODS AND RESULTS: From September 2003 to August 2005 a total of 52 patients underwent laparoscopic operations for aortoiliac disease (50 aortoiliac occlusive disease; two abdominal aortic aneurysm). The modified TDA was used in 20 patients. CONCLUSION: The main advantage of TDA is reduced dissection of the aorta and pelvic arteries resulting in lowered blood loss and lymphatic injury.
Keywords: Iliac Artery; Laparoscopy; výkony cévní chirurgie; cévy - implantace protéz; cévní protézy; laparoskopie; aorta; lidé; Blood Vessel Prosthesis; Endarterectomy; Vascular Surgical Procedures; arteria iliaca; aneurysma břišní aorty; Arterial Occlusive Diseases; Aortic Aneurysm, Abdominal; endarterektomie; Aorta; Blood Vessel Prosthesis Implantation; arteriální okluzní nemoci; Humans